ANALISIS KEMAMPUAN MENULIS CERPEN SISWA KELAS V SDN 7 MATARAM TAHUN AJARAN 2020/2021 - Farida Septiana Anwar; Muhammad Tahir; Syaiful Musaddat (Program Studi PGSD, FKIP, Universitas Mataram, 2022)
This study aims to determine the ability to write short stories for fifth grade students of SDN 7 Mataram in the academic year 2020/2021 in terms of (1) completeness of formal aspects, (2) story elements such as themes, characters, setting and plot, (3) effective sentences, use of spelling, and coherence between paragraphs. The type of research used is descriptive qualitative research. The population in this study was the population in this study were all students of class VB at SDN 7 Mataram. The data sampling technique in this research is purposive sampling. While the data collection method used documentation analysis in the form of short stories by students. The instrument used in this research is the short story assessment rubric which has been validated by experts usingtechniques expert judgment. The data analysis used iscontent analysis because this study will analyze short stories (short stories) for fifth grade students at SDN 7 Mataram. The results of the students' short story analysis showed that in terms of the completeness of the formal aspects, the fifth grade students of SDN 7 Mataram obtained 38.75% results, and were included in the low category, in terms of story elements they were in the very good category because the average obtained was very good. which is 96.25%, in terms of effective sentences, it can be categorized as sufficient because the average value is 62.5%, in terms of spelling usage, which is 81.25%, it is in the good category, in terms of the aspect of inter-paragraph cohesiveness, it is categorized as very good because it is average. the average score is 91.25%. The results of the average value of 20 short stories by class V students of SDN 7 Mataram in terms of completeness of formal aspects, the existence of short stories elements, effective sentences, completeness of spelling, and coherence between paragraphs is 73.25%, it can be concluded that the ability to write short stories of class students V SDN 7 Mataram is in quite good category.